Proposed standard model and consistent terminology for monitoring and outcome evaluation in different dietetic care settings: Results from the EU-sponsored IMPECD project. Issue 6 (December 2018) - Vanherle, K.; Werkman, A.M.; Baete, E.; Barkmeijer, A.; Kolm, A.; Gast, C.; Ramminger, S.; Höld, E.; Kohlenberg-Müller, K.; Ohlrich-Hahn, S.; Walters, M.E.; Wewerka-Kreimel, D.; et al.
Summary: Background & aims: Dietetic interventions contribute to certain health objectives and other outcomes, but are mostly part of a multimodal and multidisciplinary approach what makes evaluating the actual effects of dietitians' involvement rather complex. Although monitoring and outcome evaluation (M&OE) can provide routine data to prove the effectiveness of dietetic interventions, this has not been established yet in different dietetic settings. Methods: A comprehensive framework for M&OE in dietetics was developed by dietetic experts from five European higher education institutes for dietetics in the course of the EU sponsored project "Improvement of Education and Competences in Dietetics (IMPECD)". Results: Firstly, clear definitions on M&OE are proposed to facilitate the use of consistent terminology, with a specific emphasis on the term "impact" covering macro-level outcomes such as cost-effectiveness. Secondly, the Dietetic Care Process (DCP) was merged into a logic model to demonstrate the position of M&OE in relation to intervention planning and implementation, in both group and individual settings. Thirdly, selecting the appropriate indicators is indispensable to monitor and evaluate outcomes, and requires a high level of dietitians' critical reasoning. A categorized overview of indicators is provided to support this process. Lastly, the consortium developed a checklist to give dietitians a handle on what elements could be included in their M&OE plan and trigger them to perform M&OE in practice. Conclusions: Innovative M&OE models may help dietitians to demonstrate their effectiveness in improving clinical outcomes and justify their role in health care.